Superparamagnetic iron oxide-enhanced magnetic resonance for imaging cardiac inflammation. A minireview - Podroužková, Helena; Feitová, Věra; Panovský, Roman; Meluzín, Jaroslav; Orban, Marek (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2015)
BACKGROUND: Advances in nanotechnology have lead to the development of a novel contrast media for Magnetic Resonance Imaging (MRI) - the superparamagnetic iron oxide nanoparticle (SPIO). SPIO nanoparticles are used to image inflammation on the cellular level in various settings. This review covers the physicochemical characteristics of SPIO particles as well as relevant animal and clinical studies and discusses the potential of SPIO particles to image cardiac inflammation including cardiac graft rejection. METHODS: We searched the scientific biomedical databases Medline/PubMed, BioMedCentral, Google Scholar, Ovid and, ProQuest from to 2000 to 2013 for publications relevant to the topic. CONCLUSIONS: SPIO nanoparticles due to their unique properties could become a useful tool in imaging cardiac inflammation. However, the task is to find a suitable particle size and coating with corresponding pharmacokinetics, establish the right dose and MRI scan timing for individual applications.
Keywords: Heart Transplantation; rejekce štěpu; Magnetic Resonance Imaging; lidé; velikost částic; Graft Rejection; Myocardium; magnetická rezonanční tomografie; magnetické nanočástice; kontrastní látky; myokard; Contrast Media; Dextrans; Magnetite Nanoparticles; Particle Size; dextrany; transplantace srdce; Humans